PROBLEMS OF CREATION OF NEW GENERATION OF HIGHER EDUCATION STANDARDS - Добротвор, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The ways of renovation of modern higher education in accordance with the requirements of society, examples of world practice of standardization as well as the way of harmonization and alignment of national educational standards with European and the world’s are considered in the article. On the basis of the analysis, comparison and systematization of approaches to standardization in science literature, universal principles and methods, that are considered today as a guarantee of an effective professional learning, are defined